STUDY OF TYPE OF ELECTROLYTE EFFECT ON PLATINUM ELECTRO-CATALYST PERFORMANCE PREPARED BY CYCLIC VOLTAMMETRY ELECTRODEPOSITION METHOD FOR GLUCOSE OXIDATION REACTION - Mirzaie, Rasol Abdullah; Moeini, Behnam (MATTER: International Journal of Science and Technology, 2015)
There are several methods to prepare electro-catalysts for low temperature fuel cells. Platinum is used as a common electro-catalyst for this purpose. Electrodeposition method is applied for preparing platinum on modified carbon paper as electrode directly. Many parameters effect on performance of prepared electrodes. At this work, the effect of type of electrolyte in electrodeposition solution was investigated for making electro-catalyst that is be used as anode in Glucose Alkaline Air Fuel Cell (GAAFC). Cyclic voltammetry ((1.2-0.6) V vs. Ag/AgCl sat. KCl, 100 mV/S) is used as electrodeposition method. Number of CV cycles is varied 10 to 50. Electrodeposition was performed in two precursor solution (0.5 M) containing phosphate and sulfate anions. Platinum concentration in solution was 3 mM. The prepared electro-catalysts were studied for Glucose Oxidation Reaction (GOR) by CV analysis in 0.3 M glucose solution and 0.5 M KOH. Also, Electrochemical Impedance Spectroscopy (EIS) method was used. According our results, the type of anion in electrodeposition solution affects on properties of prepared platinum electro-catalyst for GOR. Optimized condition for number of CV cycles in phosphate and sulfate solutions is 10 and 40 respectively.